PERAN PEMBELAJARAN SENI TARI MUATAN SENI BUDAYA DAN PRAKARYA DALAM PENGEMBANGAN KEMAMPUAN MOTORIK SISWA KELAS IV DI MI DARUL ULUM MERKAWANG TAMBAKBOYO TUBAN TAHUNPELAJARAN 2020/2021 - Agus Fathoni Prasetyo; Yayuk Faul Luthfiya (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
Dance learning has a role in the development of motor skills, because the basic substance in dance learning is motion, and motion is the main element in the development of motor skills. Dance learning needs to be taught at the elementary school level because it has benefits for the growth and development of students, one of which is to hone motor skills. The aims of this study were (1) to find out the learning of dance, cultural arts and crafts for fourth grade students of MI Darul Ulum Merkawang? (2) To know the development of motor skills of fourth grade students of MI Darul Ulum Merkawang? (3) To determine the role of learning the art of dance, cultural arts and crafts in developing the motor skills of fourth grade students at MI Darul Ulum Merkawang?. This study uses a qualitative approach with descriptive analysis of the data that has been collected through interviews and observations. The results of the analysis show that students' motor skills can be developed by dancing, both gross motor skills and fine motor skills. There are factors that influence dance learning in developing motor skills, including human resources, infrastructure, environmental conditions, students' physical conditions, gender, motivation, and talents.